Penerapan Electronic Court di Pengadilan Agama Surabaya - Yulis Prameswari; Suci Cahaya Mustika; Muhammad Rizal Anshori; Laily Mudrika; Liana Oktavia (Ma’mal: Jurnal Laboratorium Syariah dan Hukum, 2020)
Abstract: The Supreme Court of the Republic of Indonesia has provided the latest innovation by issuing an electronic court service system. e-Court has a positive impact on society as a means of registering cases which are evidence of the commitment of the Supreme Court of the Republic of Indonesia based on PERMA Number 3 of 2018. E-Court is a centralized system meaning that the application is in the data center of the Indonesian Supreme Court which is integrated With the case tracking information system (SIPP) in the courts of first instance, lawyers are required to register to facilitate the dispute resolution process in the e-court system and is an absolute requirement to represent their clients in court. E-Court has been implemented in the Religious Courts since the existence of PERMA Number 3 of 2018 concerning Electronic Case and Trial Administration, by implementing e-filling, e-paymant, e-summon and e-litigation. Key word: E-Court, Laywers, Dispute Resolution Abstrak: Pengadilan tertinggi Republik Indonesia telah memberikan inovasi terbaru dengan mengeluarkan sistem layanan pengadilan elektronik. e-Court memiliki dampak positif pada masyarakat sebagai sarana untuk mendaftarkan kasus-kasus yang merupakan bukti komitmen Mahkamah Agung Republik Indonesia berdasarkan PERMA Nomor 3 Tahun 2018. E-Court merupakan sebuah sistem yang terpusat artinya aplikasi tersebut berada di data center Mahkamah Agung RI yang terintegrasi dengan sistem informasi penelusuran perkara (SIPP) di pengadilan tingkat pertama, para advokat diminta untuk mendaftar untuk memfasilitasi proses penyelesaian sengketa dalam sistem e-court dan menjadi persyaratan mutlak untuk dapat mewakili klien mereka di Pengadilan. E-Court diterapkan di Pengadilan Agama sejak adanya PERMA Nomor 3 Tahun 2018 tentang Administrasi Perkara dan Persidangan Secara Elektronik, dengan menerapkan e-filling, e-paymant, e-summon dan e-litigasi. Kata kunci: E-Court, Laywers, Resolusi Sengketa